Nelligan Brown: capstone - Brown, Nelligan, artist (Colorado State University. Libraries, 2015)
The artist's statement: I believe that there is a strong correlation between balance within both nature and humanity. In this series of crowns I explore power divisions based on nature's elemental forces. The tranquility of water, the growth of flora, the regeneration from fire, the solidity of the earth, and the movement of wind all work together to keep the equilibrium of life steady. They also represent different necessities in human life in order for humanity to function peacefully. In water we find peace and serenity, in flora there is growth of the mind, earth gives us steadfastness and strength, wind shows us mobility, and fire gives us needed destruction and regeneration. My crowns embody these traits, and bring elemental forces to life through the unique designs of each piece. Crowns are an indicator of power and strength, but such power must be tempered by sensitivity, knowledge, and patience, traits that are seen as more delicate within a leader. Metal is a very diverse medium that can show both great power and great delicacy. Through different techniques, I am able to convey both the strength that is inherent within the material, but also the fragility and ephemeral qualities that it can embody as well. Within each piece I seek an ideal equilibrium that is inherent in nature but sought after in humanity.
Equilibrium
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: metalsmithing and jewelry